TECTONIC NATURE AND SEISMIC RESPONSE OF TOP-BASEMENT DETACHMENT FAULTS IN MAGMA-POOR RIFTED MARGINS - Holker A.B.; Manatschal G.; Holliger K.; Bernoulli D. (My University, 2003)
Top-basement detachment faults (TBDF) represent exhumed segments of downward-concave detachments accommodating tens of kilometers of offset. TBDFs are key structures of magma-poor rifted margins, but are difficult to identify in seismic profiles, because they coincide with top-basement reflections. We have constructed realistic seismic models of an Alpine example, which were used to simulate full marine seismic surveys and to identify the seismic fingerprint of TBI)Fs in CMP-stacked and time-migrated sections. Minor extensional allochthons, which locally cap TBDFs, give rise to pronounced diffractions, which are in stark contrast to continuous reflections from uncapped segments of TBDFs. In time-migrated synthetic sections we find a continuous and constant amplitude reflection alternating with a laterally discontinuous reflection of variable amplitude. These diagnostics were also identified in the Lusigal 12 seismic profile imaging the Hobby High detachment, a TBDF in the Iberia Abyssal Plain. Using these diagnostics, small extensional allochthons and highangle faults cutting the Hobby High detachment are observed in Lusigal 12 and the entire sedimentary cover can be shown to be postrift. [PUBLICATION ABSTRACT]
Keywords: PLATE TECTONICS; LAVA